1999
DOI: 10.1038/sj.sc.3100818
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tidal volumes on the time to wean persons with high tetraplegia from ventilators

Abstract: Study design: Retrospective review of patient medical records comparing the outcomes of two groups of individuals with high-level (C3-4) tetraplegia ± those with high-volume and those with low-volume mechanical ventilation. Objectives: To determine if higher volume mechanical ventilation contributes to faster weaning from the ventilator with fewer complications in individuals with ventilator dependent high-level tetraplegia. Setting: A Model Spinal Injury Center, located in Colorado, USA, which treats patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…A retrospective concurrent cohort comparison study of SCI patients found that higher Vts (mean Vt 25.3 ml kg − 1 IBW) were associated with earlier weaning from mechanical ventilation and more rapid resolution of atelectasis than lower Vts (mean Vt 15.5 ml kg − 1 IBW). 11 A more recent retrospective review also suggested that the use of higher Vts resulted in fewer days on mechanical ventilation. 17 Large Vts prevent small-airway closure by stretching airway smooth muscle and reduce surface tension by expanding the surface area of pulmonary surfactant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective concurrent cohort comparison study of SCI patients found that higher Vts (mean Vt 25.3 ml kg − 1 IBW) were associated with earlier weaning from mechanical ventilation and more rapid resolution of atelectasis than lower Vts (mean Vt 15.5 ml kg − 1 IBW). 11 A more recent retrospective review also suggested that the use of higher Vts resulted in fewer days on mechanical ventilation. 17 Large Vts prevent small-airway closure by stretching airway smooth muscle and reduce surface tension by expanding the surface area of pulmonary surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-acute SCI patients are generally not felt to be at the same risk for ARDS, as acute SCI patients and higher Vts have been safely used in these patients for many years. 10,11,17 Current clinical practice guidelines even advocate higher Vts in SCI patients 5 because higher Vts have been associated with improved outcomes. A retrospective concurrent cohort comparison study of SCI patients found that higher Vts (mean Vt 25.3 ml kg − 1 IBW) were associated with earlier weaning from mechanical ventilation and more rapid resolution of atelectasis than lower Vts (mean Vt 15.5 ml kg − 1 IBW).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A similar approach is taken by other centres experienced in the management of tetraplegic respiratory failure and it has been shown that ventilating with at least 20 ml/kg and an interposed dead space can hasten the slow wean of tetraplegic patients on short-term ventilatory support. 4 Despite the addition of a breathing system with dead space it is often di cult to avoid a degree of respiratory alkalosis in patients with paralysis and low metabolic rates. Persons with tetraplegia may on occasion have episodes of dizziness which can usually be attributed to postural hypotension, autonomic hypere¯exia with hypertension or hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Weaning: Most patients can be weaned from the ventilator but this is often a tedious process lasting several weeks [29]. Surface FES of abdominal muscles could be used as part of the weaning program to potentially reduce weaning times and overall stays.…”
Section: A Clinical Significancementioning
confidence: 99%